Molecular Mechanisms of the RECQ4 Pathogenic Mutations - Xu, Xiaohua; Chang, Chou-Wei; Li, Min; Liu, Chao; Liu, Yilun (Frontiers in Molecular Biosciences, 2021)
The human RECQ4 gene encodes an ATP-dependent DNA helicase that contains a conserved superfamily II helicase domain located at the center of the polypeptides. RECQ4 is one of the five RECQ homologs in human cells, and its helicase domain is flanked by the unique amino and carboxyl termini with sequences distinct from other members of the RECQ helicases. Since the identification of the RECQ4 gene in 1998, multiple RECQ4 mutations have been linked to the pathogenesis of three clinical diseases, which are Rothmund-Thomson syndrome, Baller-Gerold syndrome, and RAPADILINO. Patients with these diseases show various developmental abnormalities. In addition, a subset of RECQ4 mutations are associated with high cancer risks, especially for osteosarcoma and/or lymphoma at early ages. The discovery of clinically relevant RECQ4 mutations leads to intriguing questions: how is the RECQ4 helicase responsible for preventing multiple clinical syndromes? What are the mechanisms by which the RECQ4 disease mutations cause tissue abnormalities and drive cancer formation? Furthermore, RECQ4 is highly overexpressed in many cancer types, raising the question whether RECQ4 acts not only as a tumor suppressor but also an oncogene that can be a potential new therapeutic target. Defining the molecular dysfunctions of different RECQ4 disease mutations is imperative to improving our understanding of the complexity of RECQ4 clinical phenotypes and the dynamic roles of RECQ4 in cancer development and prevention. We will review recent progress in examining the molecular and biochemical properties of the different domains of the RECQ4 protein. We will shed light on how the dynamic roles of RECQ4 in human cells may contribute to the complexity of RECQ4 clinical phenotypes.